Outcome and risk factors of complications after cranioplasty with polyetheretherketone and titanium mesh: A single-center retrospective study - Yao, Shun; Zhang, Qiyu; Mai, Yiying; Yang, Hongyi; Li, Yilin; Zhang, Minglin; Zhang, Run (Frontiers in Neurology, 2022)
Background: To compare the incidence of complications and constructive effects of cranioplasty with polyetheretherketone (PEEK) and titanium mesh after decompressive craniectomy, and to further explore potential risk factors of post-operative and post-discharge complications. Methods: A retrospective study was conducted on 211 patients who underwent PEEK or titanium mesh cranioplasty in the Department of Neurosurgery of Zhujiang Hospital, Southern Medical University between July 2017 and September 2021. Demographic data, imaging data, and postoperative complications were recorded and statistically analyzed. Long-term effects and satisfaction degree were evaluated based on following-up telephone survey. Univariate and multivariate logistic regression models were used to analyze risk factors of postoperative and post-discharge complications of PEEK and titanium cranioplasty. Results: The total postoperative complication rates of the PEEK and titanium mesh groups were 61.3% and 71.4% (p=0.120), and post-discharge complication rates were 34.7% and 36.0% (p=0.703), respectively. The incidence of intracranial pneumatosis during hospitalization (33.3% vs.6.6%,p<0.001) and epidural effusion in the titanium mesh group were significantly higher than that in the PEEK group (18.0% vs. 6.6%, p=0.011). Multivariate logistic regression analysis revealed a history of staged ventriculoperitoneal shunt was an independent risk factor for postoperative overall complications (p=0.030), while a history of concurrent ventriculoperitoneal shunt might independently be a risk of post-discharge overall complications (p=0.038); either superficial (p=0.001) or intracranial infection (p=0.001) was a risk factor for repair failure. Depressed skull defects (p=0.015) and cranioplasty with titanium cranioplasty (p<0.001) were associated with increased incidence of early intracranial pneumatosis. Conclusion: There were no differences in overall postoperative and post-discharge complication rates between the titanium mesh and PEEK. A history of staged VPS was an independent risk factor for postoperative overall complications, a history of concurrent VPS was an independent risk factor for post-discharge complications and infection was a risk factor for postoperative repair failure. Finally, depression skull defects and titanium mesh implants increased the incidence of postoperative intracranial pneumatosis. Our results aim to promote a better understanding of PEEK and titanium cranioplasty, and to help both clinicians and patients make better choices on implant materials.